2021
DOI: 10.1021/acssuschemeng.0c08308
|View full text |Cite
|
Sign up to set email alerts
|

Regulation Mechanisms of Carbon Dots in the Development of Lettuce and Tomato

Abstract: The regulation of plant growth and developmental processes by carbon dots (CDs) has been frequently reported. However, little is known about how CDs are related to the yield and nutritional quality. In this study, carbon dots, obtained by the hydrothermal method with l-cysteine and glucose, were systematically characterized and applied to lettuces and tomatoes in a hydroponic nutrient solution to comprehensively investigate the mechanism of regulation of plant development by CDs. We found that CDs could accele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 39 publications
0
52
0
Order By: Relevance
“…The O 1s spectrum of CDs (Figure 2L) and oxidized CDs (Figure 2P) fit with ∼531.3 and ∼532.4 eV peaks that are attributed to C−O and C−OH, respectively. 31 The relative level and chemical bonds of C, N, and S elements changed when CDs are oxidized, especially S changed more obviously than the other elements (Figure 2I−P). Chemical groups, such as thiol in cysteine, thioether in methionine, phenolic hydroxyl in tyrosine, and indole in tryptophan and imidazolyl, contribute to the antioxidant activity of amino acids.…”
Section: Resultsmentioning
confidence: 97%
“…The O 1s spectrum of CDs (Figure 2L) and oxidized CDs (Figure 2P) fit with ∼531.3 and ∼532.4 eV peaks that are attributed to C−O and C−OH, respectively. 31 The relative level and chemical bonds of C, N, and S elements changed when CDs are oxidized, especially S changed more obviously than the other elements (Figure 2I−P). Chemical groups, such as thiol in cysteine, thioether in methionine, phenolic hydroxyl in tyrosine, and indole in tryptophan and imidazolyl, contribute to the antioxidant activity of amino acids.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, the easy functional modification of the surface of CDs endows them with more application possibilities. In the preharvest process of crops, CDs with hydrophilic groups on the surface have been reported to promote seed germination, 37 regulate the synthesis of aquaporin in roots, 49 and promote the absorption of water and nutrients. CDs prepared with PEI as a precursor have been reported to deliver targeted disease resistance genes or biomolecules in crops 97,104 .…”
Section: Discussionmentioning
confidence: 99%
“…While studying the effects of CDs on crop growth, the cytotoxicity of CDs was explored, and the results showed low or no toxicity. 49,51,[97][98][99][100] Studies have shown that CDs can be degraded into plant hormone analogs after they were applied to plants, thus promoting plant growth. 36,37,101 However, the potential effects have been considered to be concentration-dependent, that is, low dose has a promoting effect and high dose has an inhibiting effect.…”
Section: Toxicity Evaluation Of Cds Applied To Cropsmentioning
confidence: 99%
See 2 more Smart Citations